Insights Into the Antiviral Pathways of the Silkworm Bombyx mori - Jiang, Liang (Frontiers in Immunology, 2021)
The lepidopteran model silkworm, Bombyx mori, is an important economic insect. Viruses cause serious economic losses in sericulture; thus, the economic importance of these viruses heightens the need to understand the antiviral pathways of silkworm to develop antiviral strategies. Insect innate immunity pathways play a critical role in the outcome of infection. The RNA interference (RNAi), NF-kB-mediated, immune deficiency (Imd), and stimulator of interferon gene (STING) pathways, and Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway are the major antiviral defense mechanisms, and these have been shown to play important roles in the antiviral immunity of silkworms. In contrast, viruses can modulate the prophenol oxidase (PPO), phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt), and the extracellular signal-regulated kinase (ERK) signaling pathways of the host to elevate their proliferation in silkworms. In this review, we present an overview of the current understanding of the main immune pathways in response to viruses and the signaling pathways modulated by viruses in silkworms. Elucidation of these pathways involved in the antiviral mechanism of silkworms furnishes a theoretical basis for the enhancement of virus resistance in economic insects, such as upregulating antiviral immune pathways through transgenic overexpression, RNAi of virus genes, and targeting these virus-modulated pathways by gene editing or inhibitors.